2014
DOI: 10.17161/jnah.vi1.11909
|View full text |Cite
|
Sign up to set email alerts
|

Initial Characterization of Major Histocompatibility Complex (Mhc) Class Iib Exon 2 in an Endangered Rattlesnake, the Eastern Massasauga (Sistrurus Catenatus)

Abstract: Genes of the major histocompatibility complex (MHC) play an important role in the vertebrate immune system and exhibit remarkably high levels of polymorphism, maintained by strong balancing selection. While the conservation implications of MHC variation have been explored in a variety of vertebrates, non-avian reptiles (most notably snakes) have received less attention. To address this gap and take the first steps toward more extensive population-level analyses, we cloned and sequenced MHC IIB exon 2 in an end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 52 publications
(69 reference statements)
4
4
0
Order By: Relevance
“…In each population, estimates of Tajima's D based on the MHC sequences were significantly greater than zero indicating balancing selection or population contraction (Tajima 1989). This finding is consistent with previous analyses of synonymous and nonsynonymous mutation rates in the Eastern Massasauga MHC (Jaeger et al 2014). Although we found a great deal of variation, the number of MHC alleles per individual showed an increasing trend from Cook to Piatt and Clinton counties, consistent with our microsatellite results.…”
Section: Comparison Of Neutral and Functional Variationsupporting
confidence: 93%
See 4 more Smart Citations
“…In each population, estimates of Tajima's D based on the MHC sequences were significantly greater than zero indicating balancing selection or population contraction (Tajima 1989). This finding is consistent with previous analyses of synonymous and nonsynonymous mutation rates in the Eastern Massasauga MHC (Jaeger et al 2014). Although we found a great deal of variation, the number of MHC alleles per individual showed an increasing trend from Cook to Piatt and Clinton counties, consistent with our microsatellite results.…”
Section: Comparison Of Neutral and Functional Variationsupporting
confidence: 93%
“…As predicted, the 24 putatively functional Eastern Massasauga MHC alleles were highly variable, at both the nucleotide and amino acid levels. Consistent with previous work (Jaeger et al 2014), we found an excess of nonsynonymous substitutions in the Eastern Massasauga MHC, indicating historical positive selection. Although this signature of selection was higher on the putative antigen-binding sites than the non-antigen-binding sites predicted based on the human MHC protein structure (Brown et al 1993), only three of the 14 amino acid residues predicted to bind antigens were identified as positively selected sites based on the maximum-likelihood analysis of evolutionary models.…”
Section: Characterization Of Eastern Massasauga Mhc Iib Exonsupporting
confidence: 92%
See 3 more Smart Citations